Digital Platform (Instagram & Tiktok) In Business Development For Msme Customers In Bengkulu City Case Study: Lupinut ( Bengkulu Msme) - Putri, Widia Dwi Okta; Soleh , Ahmad; Putri, Annisa Rahma (Journal of Management, Economic, and Accounting, 2025)
This research aims to analyze the role of digital platforms, particularly Instagram and TikTok, in supporting the development of micro, small, and medium enterprises (MSMEs) in Bengkulu City. The case study is Lupinut, a local MSME engaged in the production and marketing of products made from Bengkulu specialty nuts. The focus of the research is to understand how the use of both platforms can improve marketing strategies, brand awareness, and product sales growth. This research uses a qualitative-descriptive method with data collection techniques in the form of in- depth interviews, direct observation, and analysis of Lupinut's social media content. Instagram and TikTok were chosen for their interactive features, such as short videos, product photos, and live features, which support creative and engaging product promotion. The data shows that through consistent digital campaigns, Lupinut was able to reach a wider market, increase customer interaction, and build a strong brand image. Within a six-month period, this digital marketing strategy increased sales by 25% and attracted customers from various regions outside Bengkulu City.